Modified C1 lateral mass screw insertion using a threaded K-wire. A technical note. (September 2020) - Paterson, Amanda; Byrne, Stephen; Hansen, Mitchell; Kuru, Robert
Highlights: Instrumented fixation at the atlantoaxial joint is performed to stabilise the segment. C1 lateral mass screw constructs were described to reduce vertebral artery injury. Harms technique connects C1 lateral mass screws to C2 pars screws with rods. This article describes a modification using a threaded K-wire for C1 screw insertion. Avoid extensive dissection of the C2 nerve root and bleeding from the venous plexus. Abstract: Instrumented fixation of the C1-C2 motion segment is a standard surgical technique to stabilise that spinal segment. Instability at C1-C2 can arise from a number of conditions. Fixation of the C1 lateral mass usually involves dissection and exposure of the C2 nerve root and the posterior wall of the C2 lateral mass which can result in significant bleeding from the venous plexus. Whilst image guidance is increasing in accessibility, there are few public hospitals in Australia that have access to this technology. The authors describe their technique for insertion of a C1 lateral mass screw over a threaded K-wire to avoid extensive dissection of the C2 nerve root, reducing the risk of significant haemorrhage from the epidural venous plexus during the procedure. A retrospective analysis was undertaken on 18 consecutive patients who underwent C1-C2 instrumented fixation using this technique. Indications for C1-C2 instrumented fixation included traumatic injury (10 patients), failure of non-operative management of odontoid fractures (5 patients), pathological fractures of C2 (2 patients) and inflammatory conditions (1 patient). All patients underwent successful C1-C2 stabilisation using this technique. Blood loss did not exceed 400mls in any patient. There were no vertebral artery injuries and no patient experienced a neurological deterioration. The authors propose that their technique for insertion of a C1 lateral mass screw over a threaded K-wire is safe and effective with a low risk of neurological or vertebral artery injury. The technique may be considered as a slight modification of the Harm's procedure to reduce disturbance of the adjacent venous plexus and thereby reduction in intraoperative bleeding and operative time.